The process of training an important part of the development organization - Domańska, Joanna (Management and Administration Journal, 2023)
The success of any organization is highly qualified staff, which in addition to theoretical knowledge also has a baggage of experience gained in practice or in the training process. Each competent chief sees need douczenia of his subordinates regardless of job they hold. Necessary, they are necessary also in view of new technologies, which at the present time are often introduced in many companies. By training process was efficient and brought the expected results should be scrutinized targets skills and adapt location and method of training for a particular employee and responsibilities exercised on his workstation. Underdeveloped venture may bring more harm than good, and exposes the organization to costs. To prevent this, it is worth considering the possibility of the organization, to eliminate any adverse effects.